Evaluation of the levels of the markers of ineffective erythropoiesis (transforming growth factor-beta, growth differentiation factor 15 and erythropoietin) in patient with ß-thalassemia syndrome and its correlation to clinical and hematological parameters - Yousif, May; Al-Mamoori, Hind (Iraqi Journal of Hematology, 2022)
BACKGROUND: Anemia of β thalassemia results from a combination of ineffective erythropoiesis and hemolysis. This stimulates erythropoietin (EPO) production, which causes expansion of the bone marrow and may lead to serious deformities of the skull and long bones. Ineffective erythropoiesis also induces the release of growth differentiation factor 15 (GDF-15) and transforming growth factor-beta (TGF-β) which have been identiﬁed as regulators of hepcidin expression. OBJECTIVE: The objective is to evaluate the level of TGF-β, GDF-15, and EPO in patients with thalassemia syndrome. PATIENTS, MATERIALS AND METHODS: Patient samples were collected from Thalassemia Center of Ibn Al-Baladi Hospital. This study included 35 patients with thalassemia, 18 patients with beta-thalassemia major and 17 patients with beta-thalassemia intermedia. The age of studied group was 3-17 years. Twenty control healthy subjects were included for comparison who were age- and sex-matched with the patients group. Gel tube was used for collection of serum for enzyme-linked immunosorbent assay test for GDF-15, TGF-β, and EPO). RESULTS: There was a highly significant difference in GDF-15 and EPO levels among studied groups (P < 0.001). In addition, there was no significant difference in TGF-β level among studied groups (P > 0.05). TGF-β, GDF-15, and EPO were not significantly correlated to splenomegaly, hepatosplenomegaly, and frequency of blood transfusion duration in patients with beta-thalassemia major (P > 0.05), while TGF-β and EPO were significantly correlated to splenomegaly, hepatosplenomegaly in patients with beta-thalassemia intermedia but GDF-15 was not significantly correlated. In patients with beta-thalassemia major, EPO was negatively correlated to hemoglobin, packed cell volume, mean corpuscular volume, and red blood cells (RBC) count whereas GDF-15 significantly correlated to lymphocyte and neutrophil counts. TGF-β was significantly correlated to platelet count. In patients with beta-thalassemia intermedia, EPO and GDF-15 were not correlated to any hematological parameters whereas TGF-β was significantly correlated to RBC counts. CONCLUSION: Marker of erythropoiesis GDF-15, EPO was highly expressed in patient with beta-thalassemia major and beta-thalassemia intermedia as compared to the control group and this can be used as a future therapeutic goal for the suppression of ineffective erythropoiesis.